Pengaruh Nilai Tambah Sektor Industri, Sektor Manufaktur, Sektor Pertanian, dan Sektor Jasa Terhadap Pendapatan Nasional Bruto di Indonesia Periode 1992-2022 - Santri Mamonto; Muhammad Amir Arham; Fitri Hadi Yulia Akib (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
Santri Mamonto, 2024. The Influence of Added Value in the Industrial Sector, Manufacturing Sector, Agricultural Sector and Service Sector on Gross National Income in Indonesia for the 1992-2022 Period." Development Economics study program, Department of Economics, Faculty of Economics and Business, Gorontalo State University. Supervisor 1 Mr. Prof. Dr. Mumahammad Amir Arham, M.E and Supervisor II Mrs. Fitri Hadi Yulia Akib, S.E, M.E The aim of this research is to determine how much influence the added value of the industrial sector, manufacturing sector, agricultural sector and service sector has on gross national income in Indonesia for the period 1992-2022. The data used in this research is secondary data obtained from the World Bank for the period time period 1992-2022 and the unit of analysis is 38 provinces in Indonesia. This research uses multiple regression analysis using the Error Correction Model (ECM) method. The research results show that (1) Added Value in the Industrial Sector has a Positive and Significant Influence on Indonesia's National Income, meaning that increasing added value in the industrial sector has a large contribution to National Income in Indonesia. (2) The added value of the manufacturing sector has a negative and significant impact on Indonesia's national income, meaning that every increase in value in the manufacturing sector results in a decrease in national income in Indonesia (3) The added value of the agricultural sector has a positive and significant impact on Indonesia's national income, meaning an increase in value in the sector Agriculture has a large contribution to Indonesia's National Income. (4) The added value of the service sector has a positive and significant impact on Indonesia's national income, meaning that increasing the added value in the service sector has a large contribution to Indonesia's national income.